Introduction to New Zealand hard rock gold deposits and their exploration models. Issue 4 (2nd October 2019) - Christie, Anthony B.
ABSTRACT: Since the first official discovery of gold in 1852, gold has been mined in New Zealand from three main types of deposits: placer (c. 19 Moz Au), orogenic (mesothermal; c. 8 Moz Au) and epithermal (c. 11 Moz Au). Currently, gold production in New Zealand is from more than 30 placer mines (>50, 000 oz Au per annum) on the West Coast, and in Otago and Southland, and from hard-rock mines at the Macraes orogenic deposits in northeast Otago (202, 990 oz Au produced in 2018), and the epithermal deposits of the Waihi area (83, 492 oz Au produced in 2018) in the Hauraki Goldfield. The discovery of the Sams Creek intrusion-hosted gold deposit in west Nelson in 1974 has also encouraged exploration for this type of gold deposit. Exploration models for orogenic, intrusion-hosted and epithermal gold deposits have been developed addressing general deposit characteristics, mineral system models and key features for use in exploration. Orogenic deposits are hosted in Western Province Greenland Group (e.g. Reefton Goldfield) and Eastern Province Haast Schist Group (e.g. Macraes), whereas epithermal deposits are associated with Cenozoic volcanic rocks in Northland (e.g. Puhipuhi), and the Coromandel (e.g. Waihi) and Taupo (e.g. Ohakuri) volcanic zones.